REDETERMINATION OF SEMANTIC OPPOSITIONS AS ONE OF THE PRINCIPLES OF ORTHODOX LITURGICAL SERMON - Medvedev, Y.Y. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
In the theological semiotic system liturgical space and non-liturgical space are distinguished. This distinction can not but affect the semantic structure of the liturgical Orthodox sermon which is organi-cally related to the liturgical space. The object of the study is the text of the Orthodox liturgical sermon, the subject is the principles of the development of the liturgical sermon text. The theme of this article is related to one of the leading principles of the formation of such text - the principle of reinstalling semantic oppositions, which is caused by the need to prevent habitual perception of those forms whose content is due to the peculiarities of the semantic structure of commonly used language. The relevance of this article is determined by increased attention to religion as an important component of human and social life and, as a consequence, by the cognitive need to understand the nature of the church language actively entering into the reality of modern Russia and to realize scientifically the specifics of intensively renewed and developing speech genres, the central one of which is the speech genre of sermon. The source of the study is the texts of the liturgical sermons of Patriarch Kirill and Archbishop Hermogenes. The methods of the study are determined by the nature of the empirical material. The fundamentals of structural analysis were applied, implying the definition of not only the composition of the object elements, but also their interrela-tions: by segmentation, certain structural elements of sermons were identified and later combined into a cer-tain class on the basis of the discovery of certain regularities in their use. Oppositional analysis has revealed differential and integral features of the sermon structural elements. In addition, the study of the text as a whole dictates the need for a systematic method, proceeding from the understanding of the text as a sys-tem performing a specific function in the supersystem.